Transformasional Leadership Meningkatkan Tindakan Augmentatif And Alternative Comunication Pada Pasien Stroke Afasia Motorik - Dwi Febryanto; Hasib Ardani (Journal of Health (JoH), 2019)
About 21% -35% of patients with acute stroke experience aphasia or motor impairment language interpretation. Impact because of the lack of action independence of the nurse in improving Augmentative Alternative Communication (AAC) is not the fulfillment of the needs of the patient. AAC is media in the form of electronic devices, alphabet boards, drawing boards that contain the basic needs which may be designated by the patient that helps in communicating. The research method is a literature research, focused on the search of some previous research. The results of the research show that the role of transformational leadership increase the AAC in stroke patients aphasia motor through insiparasional motivation where the leader becomes an example to be emulated by subordinates, providing a strong motivation for change with guidance and training, individualizad consideration that is hear input to want to change apply the AAC, Idealized influence where the leader as a mentor who has charisma makes followers want to practice the AAC, and intellectual stimulation is to encourage the subordinates to see problems in aphasia motor can be minimized with the AAC. Thus it can be concluded that the Style of transformational leadership has a used of therapeutic AAC to nurses practice.